PEMBELAJARAN EKSTRAKURIKULER PROGRAMMING BASIS DATA MySQL DI SMAK MATER DEI PAMULANG DAN SMAK KALAM KUDUS 3, SMA SENTOSA JAKARTA BARAT - Purba, Florensa Rosani; Yesaya Nefuel Setiawan; Isaiah Nicodemus; Rita Wiryasaputra (Servirisma, 2024)
This extracurricular activity aims to introduce programming and data processing concepts to high school students using MySQL. Through this activity, students are expected to be able to understand the basics of computer programming with Java language and data processing with MySQL. In addition, this program also focuses on improving digital literacy and technical skills, which are very relevant in preparing students to face the challenges of the world of work in the digital era. Students are not only introduced to basic concepts, but are also given the opportunity to directly start programming and data processing skills in real contexts. Therefore, this activity is designed to provide a strong foundation for students who continue their interest in studying in the field of information technology or prepare for a career in the sector. Evaluations conducted through pre-tests and post-tests showed that although there were some challenges in understanding the material, students generally showed significant progress in computational thinking and problem-solving skills, which are very important in facing the complexity of the modern digital world.